Biomechanical Comparison of Suture-Button Suspensionplasty and LRTI for Basilar Thumb Arthritis. (December 2016) - Desai, Mihir J.; Brogan, David M.; Richard, Marc J.; Mithani, Suhail K.; Leversedge, Fraser J.; Ruch, David S.
Background: The purpose of this study was to compare the initial biomechanical strength of trapeziectomy and suture-button suspensionplasty (SBS) with ligament reconstruction and tendon interposition (LRTI) for thumb carpometacarpal (CMC) arthritis in a cadaveric model.Methods: Eight matched pairs of below-elbow cadaveric arms were used for this study. Each specimen was randomly assigned to either receive a trapeziectomy and LRTI (LRTI group) or trapeziectomy and SBS (SBS group). Using previously described and validated testing protocols, physiological key pinch was simulated. The thumb metacarpal was then incrementally loaded from 5 to 20 lbs, using 5-lb increments. Metacarpal subsidence during physiological key pinch and incremental loading was determined using radiographic measurements of trapezial space height.Results: The average pretesting trapezial space height did not differ significantly between the LRTI (11.9 mm) and SBS (13.7 mm) groups. After simulated physiological key pinch, the SBS group had significantly greater average trapezial space height compared with the LRTI group (8.0 mm vs 5.5 mm). For each incremental metacarpal load from 5 to 20 lbs, the SBS group had significantly greater average trapezial space height than the LRTI group.Conclusions: In a cadaveric model, SBS demonstrates greater resistance to metacarpal subsidence with immediate loading compared with LRTI.